Rehabilitation principles in mandibular osteonecrosis - Yu. A. Medvedev; E. M. Basin (Сеченовский вестник)
The aim of the paper is to present rehabilitation principles of atypical jaw osteomyelitis — osteonecrosis of lower jaw among addicts to synthetic drug desomorphine. Custom nikelid titanium plates and plexiform guides from superelastic nikelid titanium proved to be effective in reconstruction mandibular defects in drug addicts.